The Influence of Curing Residual Stress on the Strength and Fracture Rotating Speed of Composite Disc - Jasim, Haider Hadi (Basrah Journal for Engineering Sciences, 2007)
In this paper, the influence of thermal residual stress on strength and fracture rotating speed of composite disc is studied and analyzed using finite difference method and laminated plate theory for two types of reinforced composite discs (radial fiber reinforced disc and circumferential fiber reinforced disc). As a result the thermal residual stress will reduce radial and tangential stresses in radial fiber reinforced disc, while it shall increase radial stresses and decrease tangential stresses in circumferential fiber reinforced disc. The existing of residual stresses in composite disc will leads to initiation of crack and begins to propagation near the inner diameter compared to case when neglecting residual stress for cases taken in analysis. It is also verified that the finite difference method is a good tool for stress analysis of composite disc under residual stress effec